A NEW APPROACH TO THE DIFFERENTIAL DIAGNOSIS OF NON-ALCOHOLIC AND ALCOHOLIC LIVER DISEASE - Морозова, Ольга Александровна; Морозова, Александра Валерьевна; Мальцева, Нина Васильевна; Бичан, Николай Андреевич (Medicine in Kuzbass, 2022)
Differential diagnosis of non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) at the stage of steatosis presents significant difficulties in the practice of a primary care physician. Low-symptomatic manifestations and non-specific symptoms at an early stage of NAFLD and ALD development often complicate timely diagnosis, which is fraught with the progression of these common liver diseases. In the NAFLD pathogenesis lies a violation of lipid metabolism, which has a multifactorial character, including a disturbance of the synthesis of the adipose tissue hormone - leptin. Whereas in the ALD development, the effect on hepatocytes of ethanol and its metabolite, acetaldehyde, is of leading importance. The differences in the NAFLD and ALD etiopathogenesis gave rise to the study of the content of adipose tissue hormone in blood serum in the patients of the two groups compared. The aim is to study the level of serum leptin as an additional differential diagnostic criterion for non-alcoholic fatty liver disease and alcoholic liver disease. The subject of the study is the content of serum leptin in patients with NAFLD and ALD. Research methods. A comparative analysis of the serum leptin level in 108 patients with NAFLD and 80 patients with ALD was carried out, taking into account the body mass index and gender differences. Results. Significant differences in the serum leptin content in patients with NAFLD and ALD were revealed. The results obtained can serve as an additional differential diagnostic criterion between NAFLD and ALD at early stages. Conclusion. The obtained results of the study confirm the participation of the adipose tissue hormone leptin in the NAFLD development, regardless of gender differences, and can serve as a differential diagnostic criterion for NAFLD and ALD in the outpatient practice of a general practitioner. For a deeper understanding of the mechanism of the NAFLD development, it is necessary to study the polymorphism of the leptin receptor gene both in the patients with NAFLD and in the patients with ALD.